Neuropsychology - Zaidel, Dahlia W.; Barnes, Marcia (Handbook of perception and cognition (2nd ed.), 1994)
The field of neuropsychology has grown rapidly in recently years. New developments have been of interest across disciplines to cognitive, clinical, and experimental psychologists as well as neuroscientists. Neuropsychology presents a comprehensive overview of where the field stands now relative to all these disciplines. Representing the critical areas in human neuropsychology, this book begins with the history and development of the field and proceeds to discuss brain structure and function with regard to attention, perception, emotion, language, and movement. Key Features.